2021
DOI: 10.1002/smtd.202101334
|View full text |Cite
|
Sign up to set email alerts
|

Efficient CO2 Electroreduction to Ethanol by Cu3Sn Catalyst

Abstract: a key factor to evaluate the practicality of electrolysis systems with carbon footprint assessments, [7,8] the electrochemical CO 2to-ethanol production efficiency generally remains unsatisfactory, with Faradaic efficiency of ethanol production (FE ethanol ) typically below 50% and partial current densities (J ethanol ) < 200 mA cm −2 . [9,10] The generally low ethanol selectivity has been suggested due to the unfavorable adsorption of several key intermediates (i.e., *CHCHOH, *CH 2 CHOH, *CH 3 CHOH) in the et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 36 publications
1
42
0
Order By: Relevance
“…Later, we reported that CuSn alloys also displayed phase-orientated selectivity. The Cu 3 Sn phase delivered a relatively high ethanol selectivity (FE ∼ 61%), while the Cu 6 Sn 5 phase facilitated the CO 2 -to-C 1 conversion toward formate and CO . X-ray absorption fine structure data revealed that the coordinate environments and configurational entropies in these two alloy phases were distinctively different, where the lower configurational entropy in Cu 3 Sn presented a higher *CO coverage and thus a preferred ethanol selectivity.…”
Section: Recent Developments Of Cu-based Catalysts On Intrinsic Prope...mentioning
confidence: 98%
See 1 more Smart Citation
“…Later, we reported that CuSn alloys also displayed phase-orientated selectivity. The Cu 3 Sn phase delivered a relatively high ethanol selectivity (FE ∼ 61%), while the Cu 6 Sn 5 phase facilitated the CO 2 -to-C 1 conversion toward formate and CO . X-ray absorption fine structure data revealed that the coordinate environments and configurational entropies in these two alloy phases were distinctively different, where the lower configurational entropy in Cu 3 Sn presented a higher *CO coverage and thus a preferred ethanol selectivity.…”
Section: Recent Developments Of Cu-based Catalysts On Intrinsic Prope...mentioning
confidence: 98%
“…), coverage modification, and other interfacial microenvironment adjustments. In addition to the lifecycle assessment (LCA), 37 we also use techno-economic analysis to compare the market values of aqueous electrochemical systems, which are also necessary to consider for further research in this field.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the nature of XANES spectra of both the intermetallic catalysts is completely different from that of both elemental Cu foil and that of Cu 2 O indicates the entirely different chemical environment of Cu in the intermetallic compounds. [ 49 ] On the other hand, in the XANES of Ga K‐edge of Cu 9 Ga 4 (Figure 5c), there is an absorption maximum at 10 378.37 eV and a shoulder at about 10 382.46 eV, which are expected from the two types of Ga present in the system (Wyckoff position: 4e and 12i), whereas CuGa 2 shows only one absorption edge (10 378.92 eV) as it has only one type of Ga site (Wyckoff position: 2h) in the crystal structure. The position of absorption maxima of both the samples resembles that of Ga metal.…”
Section: Electrochemical Co2 Reductionmentioning
confidence: 99%
“…32 Besides, a bimetallic, low-entropy Cu 3 Sn catalyst by Shang et al revealed an impressive FE of 64% for ethanol in CO 2saturated 0.1 M KHCO 3 in a H-type electrolyzer; however, such a H-type electrolyzer is not appropriate for continuous processes in real-world operations. 33 Besides, the Cu 3 Sn catalyst demonstrated prolonged durability of 48 h at an industrial-level current density of −900 mA cm −2 in 1 M KOH in a membrane-electrode-based electrolyzer, but a much lower FE of 40% for ethanol. On the contrary, it is worth noting that the defect-site-rich Cu catalyst (Cu -DS ) proposed by Gu et al 34 has revealed remarkable electrocatalytic CO 2 RR performance with FE values of 52 and 15% for ethanol and n-propanol at −0.95 V and 100 mA cm −2 , respectively, and prolonged stability up to 30 h in an electrochemical flow cell reactor coupled with a gas diffusion electrode (GDE).…”
Section: ■ Introductionmentioning
confidence: 99%